2012
DOI: 10.1177/147323001204000139
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of a Mitochondrial Functional Score in Prostate Cancer

Abstract: OBJECTIVE: To evaluate the utility of a mitochondrial functional score in predicting the progress of prostate cancer. METHODS: This retrospective study included 72 patients (mean age 70.1 years) with prostate cancer who were treated by radical prostatectomy between October 2006 and March 2007. The epithelioglandular mitochondrial functional scores were assessed according to the Flameng grading. Patients were divided into six groups (groups 1 – 6) according to their Gleason score (Gleason score 2 – 7, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
(35 reference statements)
2
6
0
Order By: Relevance
“…, lacks the Warburg effect), but instead shunts glucose carbons toward lipogenesis [36] . This is also consistent with why prostate cancer cells have a striking increase in the number and pleomorphism of mitochondria [38] , [39] , [40] .…”
Section: Mad For Psa-activated Nicosamide Molecular Grenadesupporting
confidence: 86%
“…, lacks the Warburg effect), but instead shunts glucose carbons toward lipogenesis [36] . This is also consistent with why prostate cancer cells have a striking increase in the number and pleomorphism of mitochondria [38] , [39] , [40] .…”
Section: Mad For Psa-activated Nicosamide Molecular Grenadesupporting
confidence: 86%
“…The changes in the ultrastructure of prostate cancer secretory cells reported in the present study were consistent with previous findings ( 15 – 18 ). The current study demonstrated the high incidence of hyperchromatic nuclei and compact nucleoli in prostate cancer secretory cells.…”
Section: Discussionsupporting
confidence: 94%
“…Ultrastructural changes of prostate cancer cells compared with normal or hypertrophic prostate cells are well known and have been reported by numerous researchers (15)(16)(17)(18). It has been demonstrated that cancer prostate secretory cells present with hyperchromatosis of the nucleus, hypertrophy of the nucleus and nucleolus, an increased number of pleiomorphic mitochondria, various configurations and positions of Golgi complexes and increased amount of lipid droplets of different morphology (15).…”
Section: Morphological and Functional Alterations Of The Prostate Tismentioning
confidence: 90%
See 1 more Smart Citation
“…In order to investigate the ultrastructural integrity of individual mitochondrion, morphology was examined in synaptosomes using transmission electron microscopy. Visualized mitochondrial morphology was semi-quantified to evaluate mitochondrial quality using Flameng grading (Sun et al, 2012; Flameng et al, 1980). The Flameng mitochondrial score evaluates mitochondrial function based on the mitochondrial morphology using an ordinal scale of 1 through 5.…”
Section: Resultsmentioning
confidence: 99%